Italian Heritage and the Experience of Migration and Nostos in Canadian Poetry - Cadel, Francesca (Italian Canadiana, 2021)
The article addresses the theme of nostos by referring to the journeys of three authors of Italian heritage: Pier Giorgio Di Cicco, Mary di Michele, and Gianna Patriarca. Their poetry allows the possibility to revisit their journeys and to consider migration as a source of knowledge, and positive change, despite the many challenges involved in the mutation process, and the difficult hermeneutic of losses, necessary to reach awareness and a new sense of belonging.